UPAYA PEMANFAATAN SAMPAH ORGANIK DI RW 04 KELURAHAN TUNJUNGSEKAR KOTA MALANG - Sudiro Sudiro; Candra Dwiratna; Anis Artiyani (STIE Malangkucecwara, 2018)
The handling of garbage settlements in urban areas is largely still conventional, that is, with a waste-pick-up system. On the one hand, the quantity of waste generated is quite large, so this handling pattern has the potential to cause problems. One of them is the provision of advice and infrastructure. Most of the people in Tunjungsekar Village, especially RW 04, manage their waste with conventional and even individual patterns. Understanding of economic value and the value of other benefits is still uneven. While it is known that most of the waste can still be reused, one of which is organic waste. Where organic waste has the potential to be reused as compost. The method used in community service is counseling and assistance on the use of simple technology for the utilization of organic waste. The goal to be achieved is the occurrence of knowledge transfer in the utilization of organic waste. The work partners in community service are people in the RW 04 area, especially environmental cadres. The results of this activity were that the target community: (1) began to understand the value of organic waste use, (2) began to understand about the existence of simple technology for the utilization of organic waste, (3) began to understand the procedures for composting. The next hope is that the community can independently manage organic waste with a simple composting method.